Effect of nutritional density and season on the performance of young rabbit does before the first mating - Teixeira, Paulo Sérgio Dos Santos [UNESP]; Wechsler, Francisco Stefano [UNESP]; Moura, Ana Silvia Alves Meira Tavares [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2013)
The objective was to evaluate the effect of nutritional density and season on the performance of young rabbit does before the first mating. Forty-eight females from the Botucatu Genetic Group were used in each season (warm or cool), starting at the age of 70 days, housed in groups of four per cage up to 119 days, and reared individually from 120 to 140 days of age. The high-density diet was formulated to contain, on a 90% DM basis, 18.4% CP, 16.5% ADF and 2,500 kcal DE kg-1; whereas the low-density diet was formulated to contain 14.7% CP, 24% ADF and 2,000 kcal DE kg-1. The experiment was conducted according to a 2x2 factorial design (two diets x two seasons) with repeated measures (weeks). The high-density diet promoted lower feed intake, higher final weight, and higher daily weight gain, adjusted for constant intake. But these facts alone do not warrant using a high-density diet for growing rabbit does, because it could have a negative impact during the reproductive phase. In the warm season, there was a reduction in feed intake and an improvement in feed efficiency. Along time, however, the mean body weight of does was similar in the two seasons.

O objetivo foi avaliar o efeito da densidade nutricional e da estação sobre o desempenho de coelhas jovens antes do primeiro acasalamento. Foram usadas 48 coelhas do Grupo Genético Botucatu em cada estação (quente ou fresca) que iniciaram aos 70 dias de idade, alojadas em grupos de quatro por gaiola até os 119 dias e individualmente dos 120 aos 140 dias. A dieta de alta densidade foi formulada para conter, com base em 90% de MS, 18,4% PB, 16,5% FDA e 2.500 kcal ED kg-1; enquanto a dieta de baixa densidade foi formulada para conter 14,7% PB, 24% FDA e 2.000 kcal ED kg-1. O experimento seguiu um fatorial 2x2 (duas dietas x duas estações), com medidas repetidas (semanas). A dieta de alta densidade promoveu menor consumo, peso mais elevado e também maior ganho de peso ajustado para consumo constante. Mas estes fatos, isoladamente, não avalizam o uso de uma dieta de alta densidade para coelhas jovens, porque ela pode apresentar impacto negativo durante a fase reprodutiva. Na estação quente, houve redução do consumo de alimento e melhora da eficiência alimentar. Ao longo do tempo, no entanto, o peso médio das coelhas foi semelhante nas duas estações.
Efeito da densidade nutricional e da estação sobre o desempenho de coelhas jovens antes do primeiro acasalamento
Keywords: fibra em detergente ácido; eficiência alimentar; consumo de alimento; crescimento; peso vivo; nutrição; acid detergent fiber; feed efficiency; feed intake; growth; live weight; nutrition